Pengurusan Izin Muat Barang Berbahaya Curah Cair pada Kantor KSOP Dumai oleh PT. Pertamina Trans Kontinental Marine Dumai - Betti Angraini; Yursal Yursal; Yuna Sutria (Indonesian Maritime Researchers and Lecturers, 2026)
This research focuses on identifying how PT. Pertamina Trans Kontinental Marine Dumai processes permits for loading dangerous goods in bulk liquids in the Dumai region. The process begins when the ship notifies the ship of the hazardous cargo to be loaded. Afterward, the operational team or external services department prepares application documents to be submitted to the authorized agency, namely the Dumai Harbormaster's Office. The application process requires payment of fees included in Non-Tax State Revenue (PNBP). As a national shipping company, PT. Pertamina Trans Kontinental Marine Dumai also emphasizes the importance of fostering good cooperation with relevant agencies. This action is taken as a strategic step to ensure the proper handling of dangerous goods. Complete documentation is crucial in this licensing process. Required documents include a permit application letter and a dangerous goods manifest. The completeness and accuracy of these documents are crucial for the smooth running of the permit application process, while ensuring that each stage complies with applicable regulations.